Simulations of the Fomalhaut system within its local galactic environment - Kaib, Nathan A.; White, Ethan B.; Izidoro, André [UNESP] (My University, 2018)
Fomalhaut A is among the most well-studied nearby stars and has been discovered to possess a putative planetary object as well as a remarkable eccentric dust belt. This eccentric dust belt has often been interpreted as the dynamical signature of one or more planets that elude direct detection. However, the system also contains two other stellar companions residing ~ 105 au from Fomalhaut A. We have designed a new symplectic integration algorithm to model the evolution of Fomalhaut A's planetary dust belt in concert with the dynamical evolution of its stellar companions to determine if these companions are likely to have generated the dust belt's morphology. Using our numerical simulations, we find that close encounters between Fomalhaut A and B are expected, with an ~ 25 per cent probability that the two stars have passed within at least 400 au of each other at some point. Although the outcomes of such encounter histories are extremely varied, these close encounters nearly always excite the eccentricity of Fomalhaut A's dust belt and occasionally yield morphologies very similar to the observed belt. With these results, we argue that close encounters with Fomalhaut A's stellar companions should be considered a plausible mechanism to explain its eccentric belt, especially in the absence of detected planets capable of sculpting the belt's morphology. More broadly, we can also conclude from this work that very wide binary stars may often generate asymmetries in the stellar debris discs they host.
Keywords: Binaries: visual; Circumstellar matter; Methods: numerical; Planet-disc interactions; Planets and satellites: dynamical evolution and stability; Stars: kinematics and dynamics